The Determinant of Green Entrepreneurial Knowledge on SMEs in Indonesia - Iswanti Iswanti; Amir Machmud; Eeng Ahman; Dita Maharani Suwardi (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2020)
This study aims at analyzing factors that influence green entrepreneurial knowledge on SMEs in West Java. The variables reviewed in this study were the role of entrepreneurship education, media, public figure, and government on green entrepreneurial knowledge. It used explanatory survey to collect data. The population in this study were 4.285 SMEs engaged in the culinary industry in Bandung. The sample retrieval technique employed was the Slovin formula which resulted on 240 respondents. Furthermore, the collected data was analyzed using Multiple Regression Analysis. The results show that the influential factors in increasing green entrepreneurial knowledge are entrepreneurship education, media, public figures, and government both partially and simultaneously. These findings implied that it is essential to improve green entrepreneurial knowledge; it takes the role of media, public figures, entrepreneurship education, and government.Keywords: green entrepreneurial knowledge, media, government, SMEs